Analysis of the Effectiveness of Swallow Nest Tax in Increasing Regional Original Revenue in Luwu Regency - Dinda Eka Wulandari; Nur Afiah; Nuraisyiah (Economics and Business Journal (ECBIS), 2026)
This study discusses the effectiveness of the Swallow Nest Tax in increasing Regional Original Revenue (PAD) in Luwu Regency. The research problem focuses on the low realization of tax revenue compared to the set target and the suboptimal contribution of the swallow nest tax to PAD. The objective of this study is to analyze the level of effectiveness of the swallow nest tax and the factors influencing it. This research uses a descriptive qualitative approach with data collection techniques through interviews and documentation. Data analysis was conducted using an elasticity ratio approach and an interactive analysis model. The results show that the swallow nest tax has not been effective in increasing PAD, with an average elasticity value of -0.03% (inelastic) during the 2022–2024 period. The realization of tax revenue is still far below the established target. This condition is influenced by low taxpayer awareness, suboptimal business reporting, limited supervision, and unstable harvest yields. As a result, the tax effectiveness remains low and has not provided a significant contribution to PAD.